Osobenosti sociološkog pristupa religiji i njeno značenje / The Characteristics of a Sociological Approach to Religion and its Meaning - Karadži, Elmir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
This paper analyzes the characteristics of a sociological approach to religious phenomenon. Through the analysis of the social role of religion, seeks to point out what sociological approach makes specific in the scientific study of a social institution such as religion. Applying analytical, comparative and critical method seeks to demonstrate how social perspective looking at religion, studied and understood in relationship to social phenomena and processes on the one hand and the individual on the other. The study of religion in the era of globalization is an important dimension of social life. Religion is not manifested only in the private sphere, but also in the fields of politics, economy and culture. Religion exerted a cer ain influence on society, just as society has this feature. Just then correlate their hides sense sociological study of religion. The concept of religion is very complex in its terminological meaning. Sociologists is very difficult to determine its sui generis: the parameters that separate the religious from non-religious, religious and secular, sacred from the profane - while keeping in mind the theoretical and methodological implications of that are in sociology encounters. It is not easy to conceive all socio-psychological and spiritual dimensions of religion if one keeps in mind that it together with the society in general is evolving. In sociology, in view of the bit, the content, the role and function, are the two main perspective study religion: substantive and functional. The first relates to the will, and the other on the function of religion. The paper also points out the advantages and disadvantages of both approaches.